2013
DOI: 10.4257/oeco.2013.1701.04
|View full text |Cite
|
Sign up to set email alerts
|

Are Road-Kill Hotspots Coincident Among Different Vertebrate Groups?

Abstract: The evaluation of road-kill spatial patterns is an important tool to identify the priority of locations for mitigation measures aiming to reduce wildlife mortality on roads. Single-target or multi-species approaches are usually adopted on the implementation of such measures, although their success must be assessed. We aim to test if road-kill hotspots are coincident among different vertebrate groups. If this proves to be right, data on accidents from one group could be used to plan measures applicable to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 29 publications
1
40
1
11
Order By: Relevance
“…Following the methods of Teixeira et al (2013) and Coelho et al (2014), 2D HotSpot Identification analysis was performed using SIRIEMA (version 1.1, Laboratory of Ecology of Populations and Communities, Porto Alegre, RS, Brazil). Esocid positions were plotted on a geo-referenced map of the Rideau River centre line in SIRIEMA.…”
Section: Discussionmentioning
confidence: 99%
“…Following the methods of Teixeira et al (2013) and Coelho et al (2014), 2D HotSpot Identification analysis was performed using SIRIEMA (version 1.1, Laboratory of Ecology of Populations and Communities, Porto Alegre, RS, Brazil). Esocid positions were plotted on a geo-referenced map of the Rideau River centre line in SIRIEMA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have showed wild vertebrates roadkill aggregations in Brazil and worldwide (CLEVENGER et al, 2003;COELHO et al, 2008;CÁCERES et al, 2012;TEIXEIRA et al, 2013). Coelho and colleagues (2008) showed that roadkill of vertebrates, mammals and birds occurs in aggregated form in the Atlantic Forest.…”
Section: Discussionmentioning
confidence: 99%
“…An initial radius of 100 meters, a radius increase of 500 meters, confidence level of 95% and a thousand simulations were used. The values of initial radius and radius increment corresponded to the scale at which mitigation measures can be effective (TEIXEIRA et al, 2013). The program tests the existence or not of roadkill aggregations in different scales (COELHO et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another study determined that variations in carcass persistence could also bias survey results, as persistence was much lower in small animals and easily influenced weather conditions [129]. Other studies flagged up survey interval [130], scavenger removal [131] and species detectability [132,133] as factors that would influence survey results. Such biased surveys are particularly concerning if mortality estimates are used to determine the impact of roads and road networks on a species, and particularly when species of concern are involved.…”
Section: Survey Design and Mitigationmentioning
confidence: 99%